Lung cancer multidisciplinary team meetings: A survey of participants at a national conference - Bydder, S.; Hasani, A.; Broderick, C.; Semmens, James (Wiley-Blackwell, 2010)
Multidisciplinary meetings (MDMs) are a useful aid for the development of comprehensive treatment plans for cancer patients. However, little is known about the requirements for effective MDM function. Attendees at a national lung cancer conference who participated at least weekly in lung cancer MDMs were surveyed. The survey addressed the attendees' perceptions regarding the aims of MDMs, and for their own institutional MDMs, the importance and need for improvement for each of: (i) the attendance of nine discipline groups; and (ii) 15 aspects related to MDM function derived from the literature. The survey also asked participants if MDMs met their needs. There was a general agreement on the aims of the meetings. There was also an agreement on the importance of various groups' attendance and each of the examined aspects of MDMs. However, many respondents reported their meetings required moderate or substantial improvements in one or more areas. More than 20% of the respondents indicated improvement was required for the attendance of three discipline groups (palliative care physicians, pathologists and cardiothoracic surgeons) and 10 of the 15 examined aspects (more than half in the case of computerised databases). Only 9% of the respondents reported that none of the features surveyed needed either moderate or substantial improvement. MDMs met the needs of 79% of the respondents. We found general agreement on the aims of the meetings, the importance of various groups' attendance at MDMs and each of the examined aspects of MDMs. However, moderate or substantial improvements were thought to be required by many respondents. The performance of individual institutions' MDMs and the resources they have available to achieve their aims should be assessed and periodically reviewed. The survey applied here may provide a framework for MDM members to do this.